2015
DOI: 10.4055/cios.2015.7.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Results of Corrective Osteotomy and Treatment Strategy for Ankylosing Spondylitis with Kyphotic Deformity

Abstract: BackgroundTo report the radiological and clinical results after corrective osteotomy in ankylosing spondylitis patients. Furthermore, this study intended to classify the types of deformity and to suggest appropriate surgical treatment options.MethodsWe retrospectively analyzed ankylosing spondylitis patients who underwent corrective osteotomy between 1996 and 2009. The radiographic assessments included the sagittal vertical axis (SVA), spinopelvic alignment parameters, correction angle, correction loss, type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…In a recent study, Qian et al [ 3 ] demonstrated loss of correction of 3.6° and 2.5° in global kyphosis (GK) and LL after posterior wedge osteotomy with a mean follow-up of 3 years. Besides, Kim et al [ 7 ] reported loss of 4.8° in GK correction for AS-related kyphosis over 2 years postoperatively. In the presence of existing thoracic kyphosis, the loss of correction may place the fusion zone under tension due to the long lever arm, thereby resulting in the implant failure and progressive loss of correction [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Qian et al [ 3 ] demonstrated loss of correction of 3.6° and 2.5° in global kyphosis (GK) and LL after posterior wedge osteotomy with a mean follow-up of 3 years. Besides, Kim et al [ 7 ] reported loss of 4.8° in GK correction for AS-related kyphosis over 2 years postoperatively. In the presence of existing thoracic kyphosis, the loss of correction may place the fusion zone under tension due to the long lever arm, thereby resulting in the implant failure and progressive loss of correction [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was also observed in the retrospective study conducted by Lin et al, 20 to analyze the correlations of spinopelvic parameters with the clinical outcomes of AS patients after corrective surgery. On the contrary, Kim et al, 16 confirmed the relationship between SVA and postoperative ODI, however they denied any significant correlation between other spinopelvic parameters (PI, PT, LL and TK) and ODI.…”
Section: Clinical Outcomementioning
confidence: 92%
“…Classifications and management plans have been developed to address the spinal deformity in AS. 16,31 We believe that every patient should have its own custom made treatment plan taking in consideration several factors including: type and severity of deformity, site of maximum deformity, bone quality, amount of correction needed, general medical condition of the patient, hip condition and occupation of the patient. Variable methods have been described to estimate the correction required.…”
Section: Surgical Planningmentioning
confidence: 99%
“…The tactics of surgical treatment [14] was planned: in the first stage L3 PSO [15] (Pedicle Subtraction Osteotomy) with the maximum possible correction. The multi-level Smith-Petersen osteotomy was considered impossible [16] due to the complete ossification of both columns of the spine.…”
Section: Methodsmentioning
confidence: 99%